APLIKASI KONSEP PEMBELAJARAN ABAD KE-21 DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM (IPA) DI SEKOLAH DASAR (SD) - I Komang Wisnu Budi Wijaya; I Made Wiguna Yasa; Ni Nyoman Tri Wahyuni (STKIP Subang, 2023)
Currently, the world has entered the 21st century, marked by the recognition of information as a necessity for society and activities based on information and communication technology. In this situation, humans undoubtedly need various new skills. These skills are trained in learning, giving rise to the concept of 21st-century learning. This research aimed at analyzing the application strategies of the 21st-century learning concept in science learning at the elementary school level. This study applied the literature research model. The research data were derived from literature related to science learning and 21st-century learning. The data were analyzed using content analysis techniques. Based on the research results, the 21st-century learning can be applied in science learning at elementary schools by implementing student-centered learning models, concrete learning in a group learning atmosphere, and applying science products in the community environment.